Android programming for beginners learn all the Java and Android skills you need to start making powerful mobile applications - Horton, John (Packt Publishing, 2015)
Annotation
Includes index. - Online resource; title from title page (viewed January 25, 2016)
Keywords: Android (Electronic resource); Application software -- Development; Tablet computers -- Programming; Smartphones -- Programming; Logiciels d'application; Développement; Tablettes électroniques; Programmation; Téléphones intelligents; Programmation; COMPUTERS; Software Development & Engineering; General; Application software; Development